Laser metal deposition with spatial variable orientation based on hollow-laser beam with internal powder feeding technology. (February 2017) - Shi, Tuo; Lu, Bingheng; Shi, Shihong; Meng, Weidong; Fu, Geyan
Abstract: In this study, a hollow-laser beam with internal powder feeding (HLB-IPF) head is applied to achieve non-horizontal cladding and deposition of overhanging structure. With the features of this head such as uniform scan energy distribution, thin and straight spraying of the powder beam, the deposition in spatial variable orientation is conducted using a 6-axis robot. During the deposition process the head keeps tangential to the growth direction of the part. In the experiment, a "vase" shaped metal part with overhanging structure is successfully deposited, and the largest overhanging angle achieves 80° to the vertical direction. The "step effect" between cladding layers is completely eliminated with the best surface roughness of Ra=3.864 µm. Cross section of cladding layers with unequal height are deposited for angle change. Test results indicate that the formed part has uniform wall thickness, fine microstructure and high microhardness. Highlights: A cladding head hollow-laser beam with internal powder feeding technology is applied for metal deposition. The cladding head always points at tangential growth direction of the part during the deposition process. With this cladding head the deposition has high powder utilization. The deposited part has big inclined angle, low surface roughness, compact microstructure and high microhardness.